1963
DOI: 10.1577/1548-8659(1963)92[414:tmowta]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Movements of Walleyes Tagged as Yearlings in Lake Erie

Abstract: A total of 3,998 yearling walleyes, Stizostedion vitreum vitreum (Mitchill), were captured, tagged, and released along the south shore of western Lake Erie to determine their movements and their dispersal from a known nursery area. Four hundred ninety‐nine recoveries were made over a period of 3 years. Tagged walleyes traveled primarily north toward the islands in the Western Basin during their first year of liberation, and in succeeding years moved progressively toward the extreme western end of the lake. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Rather, effective management of mixed-stock populations requires a finer-scale approach that considers how stocks differentially contribute individuals according to local processes. This type of approach, however, requires the ability to identify the origins of individual fish, which historically has proven difficult in both marine and freshwater systems (Wolfert and Van Meter 1978;.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, effective management of mixed-stock populations requires a finer-scale approach that considers how stocks differentially contribute individuals according to local processes. This type of approach, however, requires the ability to identify the origins of individual fish, which historically has proven difficult in both marine and freshwater systems (Wolfert and Van Meter 1978;.…”
Section: Introductionmentioning
confidence: 99%
“…Walleye mature at age 2-3 in Lake Erie (Wolfert 1963) and spawn at night in small groups shortly after the ice breaks up in spring, with females depositing their eggs in a single night and males staying on the spawning grounds for up to several weeks (Scott and Crossman 1973). Some walleye groups spawn in specific tributary rivers, while other groups spawn on shallow shoals or reefs of Lake Erie (Olson and Scidmore 1962;Todd and Haas 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The largest spawning runs occur in the west, and smaller groups spawn in rivers and reefs of the central and eastern basins (Wolfert 1963;Schneider and Leach 1977). Although tagging studies have revealed relatively little overall migration, some walleye move seasonally from the west to the east (Thomas et al 2005) or west into Lake St. Clair (Ferguson and Derksen 1971;Todd and Haas 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For example, juvenile dispersal from spawning sites/natal streams and nursery grounds has been studied for Walleye (Wolfert, 1963) and Lake Sturgeon (Baker, 2006;Lord, 2007;Caroffino et al, 2009), all with the common goal of rehabilitating populations. Two techniques have been used to examine juvenile dispersal: acoustic telemetry (Lord, 2007) and mark-recapture (Wolfert, 1963;Baker, 2006; Caroffino et al, Table 2 Complete list of Laurentian Great Lakes fish movement studies (N = 112), including primary and grey literature, and key characteristics of each study.…”
Section: Reproductive Biologymentioning
confidence: 99%
“…Therefore, understanding the spatial and temporal distribution of stocked fishes can help identify management zones (Schmalz et al, 2002). Stock mixing has been made evident by spawning migrations and inter-lake movements of Yellow Perch in the southern basin of Lake Michigan (Glover et al, 2008) and Walleye from Lake Erie, Lake St. Clair, and southern Lake Huron (Ferguson and Derksen, 1971;Wolfert and Vanmeter, 1978;Haas et al, 1988;Todd and Haas, 1993;Wang et al, 2007). Todd and Haas (1993) combined mark-recapture data with genetic analysis to determine the movement of Walleye stocks between Lakes Erie and St. Clair.…”
Section: Stockingmentioning
confidence: 99%